Intercultural Latin American research on abuse in couple relationships of young university - Osorio Guzmán, Maricela; Prado Romero, Carlos; Morales Navarro, Mario; Maldonado, Horacio; Carozzo Campos, Julio Cesar; Benites Morales, Luis; Peralta , Pablo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
Dating or falling in love implies a romantic experience of bonding, commitment and support between the members of a couple within the framework of a socio-cultural context. This kind of relationship contributes to the psychosocial well-being providing people with socio-emotional development. However, in this dating period, many partners deal with situations of violence. The aim of current work was to analyze and to describe the presence, type and level of abuse in dating relationships in four Latin American countries. Method: the target group involved 1195 secondary, high school and university students aged 12 to 30 years from Argentina, Chile, Mexico and Peru. The Questionnaire Dating Abuse (CMN; Osorio-Guzmán, 2014), which contains 5 areas and α = 0.95, was applied. The study met the ethical standards of the American Psychological Association. Results: the proportion of participants was Argentina (22.9%), Chile (25.3%), Mexico (36.9%) and Peru (15%). The reliability of the instrument ranges from .93 to .95. It was found that more than 90% of the cases report low levels of abuse, and 21.5% reported family violence patterns. Conclusions: the naturalization of dating violence is verified, and it is considered essential to work on its denaturalization.